1976
DOI: 10.1128/iai.13.3.682-687.1976
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous multiplication of exfoliatin-producing staphylococci

Abstract: After subcutaneous inoculation of approximately 10(6) cocci, changes in staphylococcal populations were followed by the enumeration of organisms in excised tissues. In contrast to conventionaal Staphylococcus aureus strains, exfoliatin-producing strains were able to multiply in the subcutaneous tissues of neonatal and adult mice. Although strains capable of producing large quantities of exfoliatin were better able to proliferate than strains producing lesser amounts of toxin, it was not determined whether exfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Surprisingly, there was no local inflammatory response (119). Kapral (82) observed that staphylococci capable of eliciting SSSS were different from conventional strains because of their ability to multiply in the subcutaneous tissue of mice.…”
Section: Experimental Modelmentioning
confidence: 99%
“…Surprisingly, there was no local inflammatory response (119). Kapral (82) observed that staphylococci capable of eliciting SSSS were different from conventional strains because of their ability to multiply in the subcutaneous tissue of mice.…”
Section: Experimental Modelmentioning
confidence: 99%
“…Factors responsible for the multiplication of staphylococci in mice are not well defined. The encapsulated Smith strain (mucoid) can multiply after intraperitoneal inoculation (9,15), and certain exfoliatin-producing strains are able to proliferate in the subcutaneous tissues (17). Strain TG, a known exfoliatin producer, and the Smith mucoid strain, however, were unable to multiply in the lungs of mice.…”
Section: Discussionmentioning
confidence: 99%